A case of spondylocostal dysostosis with a fra (5) (q32) - Satar, Mehmet; Temoçin, A. Kübra; Atıcı, Aytuğ; Demirhan, Osman (The Turkish Journal of Pediatrics, 1997)
Spondylocostal dysostosis is a rare hereditary syndrome with various costal and vertebral deformities. No chromosomal abnormalities in connection with this syndrome were previously reported in literature. We report a case with spondylocostal dysostosis and chromosomal abnormality [fra (5) (q32)].